1985
DOI: 10.1136/pgmj.61.714.313
|View full text |Cite
|
Sign up to set email alerts
|

Stones in the common bile duct: experience with medical dissolution therapy

Abstract: Summary Thirty-one patients with radiolucent common bile duct stones received medical treatment. Nineteen had Rowachol, a terpene preparation, eight (42%) achieving complete stone disappearance within 3 to 48 months. Fifteen (including 3 of the above) took Rowachol with bile acid (chenodeoxycholic in 11, ursodeoxycholic in 4) for 3 to 60 months: 11 (73%) achieved complete dissolution within 18 months. Persistent symptoms and complications settled on conservative management: 8 (25%) patients requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Addition of oral ursodeoxycholic acid to biliary stenting was shown in an RCT to be ineffective for improving stone dissolution [153]. Two uncontrolled studies have suggested that addition of oral ursodeoxycholic acid plus a terpene preparation to biliary stenting might increase the stone dissolution rate [149,154].…”
Section: Temporary Stenting For Biliary Stonesmentioning
confidence: 99%
“…Addition of oral ursodeoxycholic acid to biliary stenting was shown in an RCT to be ineffective for improving stone dissolution [153]. Two uncontrolled studies have suggested that addition of oral ursodeoxycholic acid plus a terpene preparation to biliary stenting might increase the stone dissolution rate [149,154].…”
Section: Temporary Stenting For Biliary Stonesmentioning
confidence: 99%
“…172 It has been shown that the terpene preparation Rowachol, which contains menthol and menthone, 173 has cholelitholytic activity and its use has been recommended with careful monitoring for potential complications during cholesterol gallstone treatment. 174 A mechanism underlying Rowachol activity may derive from a combination of its cholelitholytic, choleretic and spasmolytic properties which would tend to facilitate the passage of common bile duct gallstones. 174…”
Section: Clinical Studies and Case Reports On The Side Effects Of Pepmentioning
confidence: 99%
“…174 A mechanism underlying Rowachol activity may derive from a combination of its cholelitholytic, choleretic and spasmolytic properties which would tend to facilitate the passage of common bile duct gallstones. 174…”
Section: Clinical Studies and Case Reports On The Side Effects Of Pepmentioning
confidence: 99%
“…All other modalities have failed to produce adequate success. Endoscopic sphincterotomy and ex traction are successful in a high percentage to patients with stones less than 2 cm [65][66][67], Those with previous surgery, bile duct stric tures and duodenal diverticulae may require a combined approach. Percutaneous cannulation and insertion of a wire into the duode num makes it possible to perform endoscopic sphincterotomy in virtually all patients.…”
Section: Ductal Stonesmentioning
confidence: 99%